2021
DOI: 10.48550/arxiv.2107.03306
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of quantum memory on quantum speed limit time

K. G Paulson,
Subhashish Banerjee,
R. Srikanth

Abstract: Quantum speed limit time defines the limit on the minimum time required for a quantum system to evolve between two states. Investigation of bounds on speed limit time of quantum system under non-unitary evolution is of fundamental interest, as it reveals interesting connections to quantum (non-)Markovianity. Here, we discuss the characteristics of quantum speed limit time as a function of quantum memory, quantified as the deviation from temporal self-similarity of quantum dynamical maps for CP-divisible as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…The quantum system dynamics in the non-Markovian regime is an active area of research for multiple reasons [3,[7][8][9][10][11]. It's known that quantum correlations are lesser susceptible to noise in non-Markovian [12] realms, and quantum memory speeds up the evolution of quantum states [13]. These cases bring out the need for detailed investigations of quantum systems in non-Markovian environments.…”
Section: Introductionmentioning
confidence: 99%
“…The quantum system dynamics in the non-Markovian regime is an active area of research for multiple reasons [3,[7][8][9][10][11]. It's known that quantum correlations are lesser susceptible to noise in non-Markovian [12] realms, and quantum memory speeds up the evolution of quantum states [13]. These cases bring out the need for detailed investigations of quantum systems in non-Markovian environments.…”
Section: Introductionmentioning
confidence: 99%
“…where Λ(t) = e −lt/2 (cosh(zt/2) + l z sinh(zt/2)) [28] is the decoherence function. The decoherence rate then becomes…”
Section: A Non-markovian Amplitude Damping and Random Telegraph Noisementioning
confidence: 99%
“…Even though there exists no direct connection between non-Markovianity, a class of which is identified by information backflow and quantum speed limit time (τ QSL ) [26], it's been shown that τ QSL could be realized as a witness of the decay-revival mechanism of quantum correlations [27] for a certain class of quantum noises. In [21,28], it has been seen that quantum non-Markovianity speeds up the evolution of quantum states, which gives an operational definition to the CP-(in) divisible non-Markovian quantum channels. From the practical point of view, τ QSL finds a lot of applications in a wide range of fields [29].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in [4] QSL time for achieving a target fidelity for driven quantum systems has been derived. The fact that the impact of the bath on a quantum system is not always detrimental in nature has sped up the research work unraveling the characteristics of open quantum systems [5], and naturally the investigation of speed of evolution under non-unitary dynamics has become an active research topic [6][7][8][9][10]. Quantum speed limit for open quantum system based on different measures has been proposed [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Quantum speed limit for open quantum system based on different measures has been proposed [11][12][13]. The investigation of QSL time realizes wide range of applications in the field of quantum information processing and technology as it reflects the nature of the physical process the quantum system undergoes [8]. Thus for example, the memory effects on the dynamics of quantum systems originating from the coupling between the system and bath results in the decay-revival mechanism of quantum correlations, which is very well captured by the quantum speed limit time for certain physical processes [7].…”
Section: Introductionmentioning
confidence: 99%